Student-organization matching system for practicum placement - Hassan, Shahizan; Yahya, Mohd Azlan; Wan Ishak, Wan Hussain; Chik, Abdul Razak (2007)
Practicum placement is a tedious and time consuming process which involves finding, matching and allocating students to the potential organization. Practicum Center (PPR) has been entrusted with a responsibility to handle and manage practicum programme for Universiti Utara Malaysia (UUM). Its main role is to handle the practicum placement and to secure the places for students who register for the practicum programme. Currently, the use of computer system in practicum placement process has reduced the cost for managing the record and to a certain extent, speed up the placement process. Nonetheless, there are a few steps during the placement process that require manual execution (e.g. matching students with relevant organizations) that causes delay. Furthermore, the SISPR itself is not a Web-based system and hence cannot be extended to be accessed by organizations that participate in the practicum programme. To deal with this limitation, a research project had been carried out resulting into the development of an innovative Web-based system for the placement process which was called Online Practicum Student Placement System (OPSP). OPSP is a student-organization matching system which acts as a gateway for organizations that participate in the practicum programme to access and browse a list of students based on their requirements. The system also allows the organizations to update their profile,select the potential students, browse students resume, confirm selection and view the final list of cqnfirrned students. Additionally, OPSP provides feedback mechanism during the execution of each phase of the placement process via an automatic notification email which will be sent to both the employers' officer incharge and respective University practicum coordinator. Based on the result of the trial run being conducted for one semester with a few selected organizations, the implementation of this innovative solution certainly contributes towards effective and economical student placement process. Furthermore,the OPSP system also provides a new business opportunity for UUM as the system can be offered to be utilized by other IPTA and IPTS with certain predetermined annual fees. Apart from that, the system can also be used by UUM's Career and Counselling Centre to assist UUM graduates in finding jobs.